2015
DOI: 10.1186/s12889-015-1707-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of a Web-based computer-tailored nutrition education intervention for adults including cognitive and environmental feedback: a randomized controlled trial

Abstract: BackgroundUnhealthy diets are prevalent in Western countries, especially among low-educated people. To have an effect on health, it is important that dietary changes are sustained over time. This study examines long-term effects of a cognitive and environmental-feedback version of a Web-based computer-tailored (CT) nutrition education intervention targeting fruit, vegetables, high-energy snacks and saturated fat.MethodsA randomized controlled trial was conducted with a basic (tailored intervention targeting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…The effect size for changes in vegetable consumption ( d = 0.37) in the present study was in line with the effect size of a Dutch web-based, CT, diet-only education intervention for adults in the general population ( d = 0.32) [ 90 ]. Also, Goode et al [ 55 ] reported comparable effect sizes ( d = 0.16 to d = 1.71) for non-face-to-face interventions on fruit and vegetable outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…The effect size for changes in vegetable consumption ( d = 0.37) in the present study was in line with the effect size of a Dutch web-based, CT, diet-only education intervention for adults in the general population ( d = 0.32) [ 90 ]. Also, Goode et al [ 55 ] reported comparable effect sizes ( d = 0.16 to d = 1.71) for non-face-to-face interventions on fruit and vegetable outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, a lifestyle intervention in Sweden using counseling, group discussions on healthy eating by health workers and cooking classes by a chef to increase fruit and vegetable intake and to reduce fat intake, could not produce a significant change in behaviour outcomes [49]. Similarly, a 9-months web-based computer-tailored intervention aimed at increasing fruit and vegetable intake and decreasing saturated fat intake, did not result in significant intervention effects among Netherland adults [50]. Compared to the present study, interventions on reducing fat and sugar intake demonstrated higher effect on weight reduction [13,51].…”
Section: Discussionmentioning
confidence: 87%
“…All studies were performed in high-income countries, with the majority ( n = 11) held in the United States ( 23 , 25 , 26 , 29 33 , 37 , 38 , 40 ), followed by the Netherlands ( n = 5) ( 27 , 28 , 36 , 39 , 42 , 43 ), with the rest comprised of Australia, the United Kingdom, Italy, France, and a single trial conducted in multiple European countries. There were 21,262 participants in total.…”
Section: Resultsmentioning
confidence: 99%
“…Where the information was provided, ages ranged from 18 to 79 y with the average number of participants at baseline being 818 (median 517), dropping to 598 (median 456) at study completion. Participants were found from: the general population in 6 studies ( 25 , 28 , 35 , 36 , 42 , 43 , 49 ); those with risk factors such as obesity or diabetics ( n = 4) ( 38 , 45 47 ); employees ( n = 5) ( 24 , 27 , 39 , 41 ); recruited from healthcare networks, e.g., primary care patients ( n = 4) ( 23 , 29 , 33 , 37 ); those with low income ( n = 3) ( 26 , 30 , 31 ); and the 4 remaining used students ( 40 , 48 ), internet shoppers ( 34 ), and those who wished to improve their diet ( 44 ).…”
Section: Resultsmentioning
confidence: 99%